Flexible Glass Hybridized Colloidal Quantum Dots for Gb/s Visible Light Communications - Caroline Foucher; Mohamed Islim Sufyan; Benoit Jack Eloi Guilhabert; Stefan Videv; Sujan Rajbhandari; Ariel Gomez Diaz; Hyunchae Chun; Dimali A. Vithanage; Graham A. Turnbull; Ifor D. W. Samuel; Grahame Faulkner; Dominic C. O'Brien; et al. (IEEE Photonics Journal, 2018)
Color converting films of colloidal quantum dots (CQDs) encapsulated with flexible glass are integrated with microsize GaN LEDs (μLEDs) in order to form optical sources for high-speed visible light communications (VLC). VLC is an emerging technology that uses white and/or colored light from LEDs to combine illumination and display functions with the transmission of data. The flexible glass/CQD format addresses the issue of limited modulation speed of typical phosphor-converted LEDs while enhancing the photostability of the color converters and facilitating their integration with the μLEDs. These structures are less than 70 μm in total thickness and are directly placed in contact with the polished sapphire substrate of 450-nm-emitting μLEDs. Blue-to-green, blue-to-orange, and blue-to-red conversion with respective forward optical power conversion efficiencies of 13%, 12%, and 5.5% are reported. In turn, free-space optical communications up to 1.4 Gb/s VLC is demonstrated. Results show that CQD-converted LEDs pave the way for practical digital lighting/displays with multi-Gb/s capability.